PENGARUH POLA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS PEGAWAI (Universitas Muhammadiyah Palembang, 2023)
Purpose– This study aims to measure the effect of leadership patterns on productivity, work environment on work productivity partially and simultaneously measure work environment leadership patterns on employee productivity in the Department of Transportation of East Kalimantan Province simultaneously Design/methodology– The type of research in this research is a quantitative approach. The population in this study were 79 employees with the status of civil servants at the Department of Transportation, East Kalimantan Province. The sample used in this study is the entire population, namely 79 employees. The sampling technique is a saturated sample technique. Data analysis techniques using Data Instrumentation Techniques, Multiple Linear Regression Analysis Techniques, Classical Assumption Techniques, Hypothesis Testing. Data processing used the SPSS (Statistics Package for Social Sciences) software program, version 25. Data collection techniques were conducted by interviewing and distributing questionnaires. The measurement scale used is the Likert scale. Findings - The research results show that leadership patterns and the work environment both simultaneously and partially have a significant effect on employee productivity